Gluteal Region Plasmablastic Lymphoma in a Crohn's Disease Patient Treated with Anti-Tumor Necrosis Factor and Immunosuppressive Therapies: Report of a Rare Case with Literature Review. (9th November 2022) - Sadough Shahmirzadi, M; Fakhri, N; Jetly, R; Loganantharaj, N
Abstract: Introduction/Objective: Plasmablastic lymphoma (PBL) is rare, initially described in the oral cavity of HIV patients but can affect other extra-nodal sites and immunodeficiency states. We report an unusual case of PBL in an HIV negative Crohn's disease (CD) patient with prior anti-tumor necrosis factor (TNF) and immunosuppressive therapies including prednisone. Methods/Case Report: A 54-year-old man with recent bleeding from chronic gluteal wounds had CD (five years), a left-lower-quadrant diverting colostomy (three years) and treatment with adalimumab (three years), briefly with infliximab (discontinued after an infusion reaction) and chronic prednisone. Multiple perianal fistulous tracts were present and biopsied. Dermal diffuse infiltrate of pleomorphic plasmacytoid cells had prominent nucleoli, and an immunohistochemical profile as: CD20-/CD22-/CD30-/CD38-/CD45-/CD56+(weak, subset)/CD79a-/CD138+/EBV+(EBER-ISH)/HHV8-/kappa+/lambda-/MUM1+/PAX5-/Ki-67(70-80%) confirming PBL. Chemotherapy with bortezomib combined with etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin resulted in a good response. Results (if a Case Study enter NA): NA. Conclusion: A meta-analysis found increased risk of non-Hodgkin lymphomas in CD treated with anti-TNFs, however, lymphoma subtypes were not specified. Seven cases of CD-associated PBL were found in the literature (from 2007). Of all cases 6 were men and 2 women with an average age 49 years (range 32-65), HIV negativity documented in five, involvement sites of gastrointestinal tract (5), perianal skin (2) and paravertebral soft tissue (1), and treatments with anti-TNFs (6), 6-mercaptopurine+budesonide (1) and salazosulfapyridine (1). The average intervals from CD and anti-TNFs to PBL were 14.5 years (range 5-30) and 17 months (range 4-36) respectively. Increased PBL risk may be related to the disease itself, anti-TNF/immunomodulator therapies, EBV reactivation, or other host-related factors. Investigations for potential risks of CD therapies can ensure their safe use in susceptible patients.